ASNF-M / SiO2 (at) CPs hybrid copolymerization gel and preparation method thereof

Through the preparation method of ASNF-M/SiO2@CPs hybrid copolymer gel, the problems of poor functionality, poor dispersion, low tensile strength and insufficient stability of traditional materials are solved, and hybrid gel materials with high performance stability and versatility are achieved, which are suitable for multi-field applications.

CN119708370APending Publication Date: 2025-03-28YANCHENG YOUPU ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938753.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional low-dimensional nanoparticles and hybrid gel materials have problems such as poor functionality, poor dispersion, low tensile strength, loose crosslinking network and insufficient long-term stability, which limits their application in functional fibers and large-scale applications.

Method used

The preparation method of ASNF-M/SiO2@CPs hybrid copolymer gel is adopted to generate M-CPs coordination polymer hybrid material through hydrothermal reaction, and combined with carboxylated cellulose nanofibers and bifunctional group coordination polymer to form a hybrid gel material with integrated structural functions.

Benefits of technology

It has achieved hybrid gel materials with high environmental adaptability, high performance stability, good mechanical elasticity, high strength, high elastic modulus, hydrophobicity and controllable chemical structure, solving the shortcomings of traditional materials and is suitable for applications in multiple fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708370A_ABST
    Figure CN119708370A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of gel, in particular to ASNF-M / SiO2 (at) CPs hybrid copolymerization gel and a preparation method thereof. The preparation method comprises the following steps: adding an M-CPs coordination polymerization hybrid material and ASNF hydrogel into an aqueous solution containing acrylamide, bisacrylamide and ammonium persulfate to form a suspension; and dispersing the SiO2 microspheres into the formed suspension, and performing freeze drying to obtain ASNF-M / SiO2 (at) CPs hybrid copolymerization gel. According to the invention, the mesoporous SiO2 microspheres and organic components form a micro-mechanical interlocking effect; a multifunctional M-CPs coordination polymerization hybrid material is introduced, the problem of interfacial compatibility is solved, carboxylated cellulose nanofibers and a bifunctional coordination polymer are successfully converted into a high-performance hybrid gel material, and the high-performance hybrid gel material has the advantages of high environmental adaptability, high performance stability, high hydrophobicity, controllable chemical structure and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gels, and in particular to an ASNF-M / SiO2@CPs hybrid copolymer gel and a preparation method thereof. Background Art

[0002] At present, traditional low-dimensional nanoparticles and hybrid gel materials mainly have the following problems:

[0003] (1) Traditional low-dimensional nanoparticles have no functionality and poor dispersibility, which easily leads to agglomeration, resulting in low efficacy;

[0004] (2) The tensile strength of traditional nanocomposite hydrogel materials is generally less than 1 MPa. When processed into low-dimensional materials (such as membrane materials, fiber materials, etc.), it is difficult to withstand external force fields;

[0005] (3) After the polymerization of the monofunctional gel monomer, due to its linear or comb-like molecular chain structure, compared with chemical crosslinking, the crosslinking network is loose and difficult to withstand tensile stress, so it cannot be used for fiber construction, which greatly limits the fiber hybrid gel construction of a large number of functional monomers;

[0006] (4) Traditional hybrid gels lack long-term stability under various realistic environmental conditions and are easily decomposed, resulting in performance failure and reverse reactions, which hinders their large-scale application. Summary of the invention

[0007] The purpose of the present invention is to provide an ASNF-M / SiO2@CPs hybrid copolymer gel and a preparation method thereof in view of the above-mentioned deficiencies in the prior art.

[0008] A method for preparing an ASNF-M / SiO2@CPs hybrid copolymer gel of the present invention comprises the following steps:

[0009] S1, 4'-phosphinobiphenyl-4-carboxylic acid, zinc acetate and N,N'-dimethylformamide solution were mixed and then hydrothermally reacted to generate M-CPs coordination polymerization hybrid material;

[0010] S2, mixing the carboxylated cellulose nanofiber suspension and sodium alginate and freeze-drying the mixture to obtain a SNF polymer, and immersing the aerogel in a calcium chloride solution for cross-linking to obtain a cross-linked SNF polymer;

[0011] S3, soaking the cross-linked SNF polymer obtained in step S2 in a mixed solution containing N-isopropylacrylamide, N,N'-methylenebisacrylamide, an initiator, and CNTs, and after vacuum drying, quickly dripping N,N,N',N'-tetramethylethylenediamine therein, and polymerizing at room temperature after freezing polymerization to obtain ASNF hydrogel;

[0012] S4, adding the M-CPs coordination polymerization hybrid material and ASNF hydrogel into an aqueous solution containing acrylamide, bisacrylamide, and ammonium persulfate to form a suspension;

[0013] S5, dispersing SiO2 microspheres into the suspension formed in step S4, and freeze-drying to obtain ASNF-M / SiO2@CPs hybrid copolymer gel;

[0014] There is no order of precedence for steps S1 and S2.

[0015] Furthermore, in step S1, the mass ratio of 4'-phosphinobiphenyl-4-carboxylic acid to zinc acetate is 25-30:30-35; and in the N,N'-dimethylformamide solution, the volume ratio of N,N'-dimethylformamide to water is 9:1.

[0016] Furthermore, in step S3, in the mixed solution, the mass ratio of the cross-linked SNF polymer, N-isopropylacrylamide, N,N'-methylenebisacrylamide, initiator and CNTs is 300-350:1000:2:25:1-2.

[0017] Furthermore, in step S4, the mass ratio of the M-CPs coordination polymerization hybrid material and the ASNF hydrogel is 15-20:280.

[0018] Furthermore, in step S4, the mass ratio of acrylamide, bisacrylamide and ammonium persulfate is 18-20:1:20-25, and the concentration of acrylamide is 0.12-0.18 g / ml.

[0019] Furthermore, in step S5, the concentration of SiO2 microspheres in the suspension is 0.2-0.3 g / ml.

[0020] Furthermore, in step S3, the polymerization is performed at -18°C for 18-20 hours and then at room temperature for 4-5 hours.

[0021] Furthermore, in step S5, the mixture is frozen at -80°C for 24 hours and then dried at room temperature for 48 hours.

[0022] Further, in step S1, 4'-phosphinobiphenyl-4-carboxylic acid is prepared by the following method:

[0023] (1) Add 200 mL of dried tetrahydrofuran (THF) to 4,4'-biphenyl dibromide under Ar gas protection and stir for 5-10 minutes to obtain solution a;

[0024] (2) cooling solution a to -78°C, adding butyl lithium dropwise, stirring vigorously, and then standing at low temperature to obtain solution b;

[0025] (3) adding excess concentrated HCl dropwise to solution b, stirring vigorously, then adding dichloromethane dropwise, stirring for 5-10 minutes, and filtering to obtain a white solid powder product 4'-bromobiphenyl-4-carboxylic acid;

[0026] (4) After mixing 4'-bromobiphenyl-4-carboxylic acid and methanol, concentrated H2SO4 was added dropwise, and the mixture was refluxed at 75°C overnight. After cooling, the methanol was removed by spinning and filtered to obtain a white solid powder product, 4'-bromobiphenyl-4-carboxylic acid methyl ester;

[0027] (5) 4'-bromobiphenyl-4-carboxylic acid methyl ester, diethyl phosphate, palladium acetate, triethylamine, triphenylphosphine and dried toluene were added to a three-necked flask in sequence, and refluxed overnight under Ar gas protection to obtain a turbid solution c;

[0028] (6) Add activated carbon to solution c for reflux decolorization, filter out the black solid, wash and filter with 1:2 ethyl acetate-petroleum ether solution, and dry to obtain a milky white solid powder of 4'-diethyl phosphite-bromobiphenyl-4-carboxylic acid methyl ester;

[0029] (7) 4'-Diethylphosphite-bromobiphenyl-4-carboxylic acid methyl ester, deionized water, concentrated HCl and dimethyl sulfoxide (DMSO) were added into a round-bottom flask in sequence, refluxed at 100° C. overnight, and filtered and dried to obtain 4'-phosphinobiphenyl-4-carboxylic acid.

[0030] An ASNF-M / SiO2@CPs hybrid copolymer gel prepared by the above-mentioned preparation method.

[0031] The present invention uses inorganic nanoparticles (M-CPs) with specific intrinsic functions (SiO2) and different functional groups on the surface as active cross-linking points, and adopts free radical polymerizable polymers (ASNF) as organic structural units to design and construct a hybrid gel material with integrated structure and function. The preparation method is environmentally friendly and efficient, with a simple process and high cost performance.

[0032] The present invention is based on cross-scale (molecule-nano-micrometer) interface structure design, through the cross-scale experiment of "inorganic particles + hydrogel + coordination polymer", adopting the techniques of molecule selection, interface regulation and porous structure assembly, that is, utilizing the low cross-linking density hybrid silicon source at the molecular scale, the network interface coupling of carboxylated cellulose nanofibers and bifunctional coordination polymers at the nanoscale, and the cellulose nanofiber bridged hydrogel network structure at the micrometer scale, to prepare an ASNF-M / SiO2@CPs hybrid copolymer gel, and at the same time, on this basis, establish a new method for preparing inorganic / organic-polymer composite hybrid gel.

[0033] The ASNF-M / SiO2@CPs hybrid copolymer gel prepared by the present invention forms a micromechanical interlocking effect between mesoporous SiO2 microspheres and organic components; multi-dimensional, multi-structural and multifunctional inorganic nanoparticles are prepared for the construction and functional modification of organic hybrid gel materials, that is, the multifunctional M-CPs coordination polymerization hybrid material is introduced to solve the problem of interface compatibility, so that it has anisotropic micro and macro structures; and carboxylated cellulose nanofibers and bifunctional coordination polymers (4'-phosphinobiphenyl-4-carboxylic acid) are successfully converted into high-performance hybrid gel materials, and the structure of fiber-reinforced composite materials is used to enhance the gel structure, so that it has the advantages of high environmental adaptability, high performance stability (good mechanical elasticity, high strength, high elastic modulus), high hydrophobicity and controllable chemical structure.

[0034] This invention provides an efficient, inexpensive and scalable path for the development of hybrid materials based on rich cellulose and coordination polymers, which can be widely used in clean energy, smart responsive materials, national defense and military industry, energy management, civil construction and other fields. This breakthrough is expected to have a significant market impact in a short period of time. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Schematic diagram of the synthesis process of the prepared bifunctional coordination polymers (CPs);

[0036] Figure 2 is the SEM of the prepared ASNF hydrogel;

[0037] Figure 3 is the anisotropic mechanical property of ASNF hydrogel;

[0038] Figure 4 Schematic diagram of freeze-drying of the prepared ASNF-M / SiO2@CPs hybrid copolymer gel;

[0039] Figure 5 The actual picture of the prepared ASNF-M / SiO2@CPs hybrid copolymer gel;

[0040] Figure 6 The material properties of the prepared ASNF-M / SiO2@CPs hybrid copolymer gel;

[0041] Figure 7 This is the SEM image of ASNF-M / SiO2@CPs hybrid copolymer gel. DETAILED DESCRIPTION

[0042] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0043] Example 1

[0044] The preparation method of bifunctional coordination polymers (CPs) comprises the following steps:

[0045] (1) 15 g of 4,4'-biphenyl dibromide (48 mmol) was placed in a 250 mL three-necked flask, and 200 mL of dried tetrahydrofuran (THF) was added under Ar gas protection, and stirred for 5-10 minutes to obtain solution a;

[0046] (2) Place solution a in a reaction box filled with dry ice-acetone, lower the temperature to -78°C, and add 18 mL of 2.5 mol·L -1 butyllithium (LiC4H9, 48 mmol), stirred vigorously for 25-30 minutes, transferred to a large beaker with dry ice and allowed to stand for 20-30 minutes to obtain solution b;

[0047] (3) Add excess concentrated HCl dropwise to solution b, stir vigorously for 10-15 minutes, then add 25 mL of dichloromethane (CH2Cl2) dropwise, stir for 5-10 minutes and filter to obtain 10.5 g of a white solid powder product, 4'-bromobiphenyl-4-carboxylic acid;

[0048] (4) 10.5 g of 4'-bromobiphenyl-4-carboxylic acid and 150 mL of methanol were added to a 250 mL round-bottom flask, and 7 mL of concentrated H2SO4 was added dropwise. The mixture was refluxed at 75°C overnight. After cooling, the methanol was removed by spinning and filtered to obtain 9.52 g of a white solid powder product, 4'-bromobiphenyl-4-carboxylic acid methyl ester;

[0049] (5) 9.52 g of 4'-bromobiphenyl-4-carboxylic acid methyl ester, 4.56 g of diethyl phosphate, 0.5 g of palladium acetate, 3.32 g of triethylamine, 3.46 g of triphenylphosphine and 100 mL of dried toluene were added sequentially into a 250 mL three-necked flask, and refluxed overnight under Ar gas protection to obtain a turbid solution c;

[0050] (6) Activated carbon was added to the turbid solution c for reflux decolorization, the black solid was filtered out, washed and filtered with a 1:2 ethyl acetate-petroleum ether solution, and dried to obtain 7.10 g of a milky white solid powder of 4'-diethyl phosphite-bromobiphenyl-4-carboxylic acid methyl ester;

[0051] (7) 7.10 g of 4′-diethylphosphite-bromobiphenyl-4-carboxylic acid methyl ester, 180 mL of deionized water, 15 mL of concentrated HCl, and 70 mL of dimethyl sulfoxide (DMSO) were added sequentially into a 500 mL round-bottom flask, refluxed at 100 °C overnight, and filtered and dried to obtain 5.7 g of 4′-phosphinobiphenyl-4-carboxylic acid (4,4′-pbpca), i.e., bifunctional coordination polymers (CPs).

[0052] The schematic diagram of the synthesis process of the bifunctional coordination polymer (CPs) prepared in this example is shown in Figure 1 .

[0053] Example 2

[0054] The preparation method of M-CPs hybrid material comprises the following steps:

[0055] (1) 0.28 g of 4,4'-pbpca and 0.33 g of zinc acetate (Zn(OAc)2·2H2O) were sequentially added to a mixed solvent of 9 mL of N,N'-dimethylformamide (DMF) and 1 mL of deionized water in a stoichiometric ratio of 3:2:2318:1112, and stirred at room temperature for 1.5-2 hours to obtain a white solution d;

[0056] (2) Solution d was transferred to a 15 mL stainless steel reactor lined with polytetrafluoroethylene, reacted in a thermostat at 180 °C for 7 days, naturally cooled to room temperature, washed with excess deionized water, filtered, and dried to obtain 0.34 g of M-CPs hybrid material.

[0057] Example 3

[0058] The preparation method of SiO microspheres comprises the following steps:

[0059] (1) 47 mL of ethanol, 3 mL of deionized water, and 8 mL of aqueous ammonia were added to a 250 mL beaker in sequence, and after magnetic stirring for 5-10 minutes, 6 mL of tetraethyl orthosilicate (TEOS) was added, and stirring was continued at 60° C. for 2-3 hours to obtain solution e;

[0060] (2) Solution e was transferred to a centrifuge at a centrifugal speed of 8000 r·min-1 to extract a white precipitate, and after being washed several times with deionized water and ethanol, the solution was transferred to a centrifuge at a centrifugal speed of 8000 r·min-1 to extract a white precipitate, and then placed in a drying oven at room temperature for 1-2 hours to obtain mesoporous SiO microspheres.

[0061] Example 4

[0062] The preparation method of ASNF hydrogel comprises the following steps:

[0063] (1) A mixture containing a carboxylated cellulose nanofiber (NF) suspension (25 mg / mL) and a sodium alginate (SA) solution (20 mg / mL) was dropped into a silica gel mold, which was placed in a foam box filled with liquid nitrogen and frozen for 30 minutes, and then transferred to a freeze dryer (pressure: 10 Pa, temperature: -56°C) for freeze drying for 48 hours to obtain a solid SNF polymer;

[0064] (2) soaking the solid SNF polymer in an ethanol solution of calcium chloride (20 mg / mL) for 10 minutes, washing with sufficient deionized water, and drying at room temperature for 20-30 minutes to obtain a calcium ion cross-linked SNF polymer;

[0065] (3) 340 mg of the calcium ion cross-linked SNF polymer was immersed in a 5 mL solution containing 1 g of NIPAM monomer (N-isopropylacrylamide), 2 mg of MBAA cross-linking agent (N,N'-methylenebisacrylamide), 25 mg of K2S2O8 initiator and 1.2 mg of CNTs for 1 minute, and dried in a vacuum dryer (pressure: -0.1 MPa) for 3-5 minutes to obtain a polymerizable mixture f;

[0066] (4) 20 μL of N,N,N',N'-tetramethylethylenediamine (TEMED) accelerator was quickly dropped onto the surface of the polymerizable mixture f, transferred to a cold plate at -30 °C and frozen for 3-5 minutes, then taken out and placed in a refrigerator (-18 °C) for freeze polymerization for 18-20 hours, and then polymerized at room temperature for 4-5 hours to obtain ASNF hydrogel.

[0067] The SEM image of the ASNF hydrogel prepared in this example Figure 2 The anisotropic mechanical properties of ASNF hydrogels are shown in Figure 3 , where the left figure shows the tensile stress-strain curves in the parallel and perpendicular directions; the right figure shows the stress and Young's modulus calculated based on the tensile stress-strain curves.

[0068] Example 5

[0069] The preparation method of ASNF-M / SiO2@CPs hybrid copolymer gel comprises the following steps:

[0070] (1) Add bisacrylamide solution to 0.156g / ml acrylamide solution, add 10% ammonium persulfate solution during stirring, the amount of which accounts for 23% of the mass of the mixed system, the mass ratio of acrylamide to bisacrylamide is 19:1, degas for 5 minutes, and add M-CPs hybrid material and ASNF hydrogel in a mass ratio of 17:280 in sequence to form a suspension g, the concentration of M-CPs hybrid material and ASNF hydrogel in the suspension is;

[0071] (2) SiO2 microspheres were added to the suspension g, the concentration of SiO2 microspheres in the suspension was 0.28 g / ml, and the mixture was vigorously stirred for 5-10 minutes to make it completely dispersed. The resulting mixture was poured into a round mold, frozen at -80°C for 24 hours and then dried for 48 hours to obtain ASNF-M / SiO2@CPs hybrid copolymer gel.

[0072] The freeze-drying schematic diagram of the ASNF-M / SiO2@CPs hybrid copolymer gel prepared in this example is shown in Figure 4 ;

[0073] See the actual picture Figure 5 , Figure 5 a is a real picture of the object placed for 1 day. Figure 5 b is the actual picture after being placed for 28 days.

[0074] The performance of the ASNF-M / SiO2@CPs hybrid copolymer gel prepared in this example is shown in Figure 6 , Figure 6 Material properties of ASNF-M / SiO2@CPs hybrid copolymer gel; (a) particle size; (b) sinusoidal fitting curve of angular displacement; (c) compressive-flexural strength, from Figure 6 a It can be seen that the central value of the particle size distribution is 6.7±1.9nm, indicating that the material has a relatively uniform particle size distribution. The small size and narrow distribution range of the particles may enhance the specific surface area and interface effect of the material, thereby contributing to its performance improvement in composite materials (such as mechanical properties and thermal stability). Figure 6 b It can be seen that the shape of the curve conforms to the characteristics of a sine wave, indicating that the angular displacement response of the material shows good periodicity and regularity; the peak values ​​and phases of the two fitting curves are different, which verifies that the response of the material under dynamic load is predictable, providing data support for its application in dynamic mechanical environments. Figure 6 c It can be seen that the compressive strength increases significantly with the curing time (1, 3, 7, 14 and 28 days), indicating that the strength of the material gradually increases under long-term curing and reaches the maximum value at 28 days, reflecting the further solidification and stabilization of the gel network and composite structure; the flexural strength shows a similar trend to the compressive strength, but the increase rate is slower than that of the compressive strength, proving that its structural stability is enhanced and it has the potential for long-term application.

[0075] Figure 7 The SEM image of ASNF-M / SiO2@CPs hybrid copolymer gel. Figure 7 It can be seen that the material exhibits graded porous properties from macro to micro, with a gradual network from large pores to micro pores. Large pores help improve the efficiency of molecular and ion transmission, while small pores improve the activity and energy storage capacity of the material. The pore wall structure is uniform and reasonably distributed, which not only ensures mechanical strength and enhances the stability of the material by increasing the specific surface area of ​​the material, but also helps to disperse stress, thereby improving its performance under compression and dynamic loads.

[0076] For matters not mentioned above, the prior art applies.

[0077] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing ASNF-M / SiO2@CPs hybrid copolymer gel, characterized in that: The steps include: S1, 4'-phosphinobiphenyl-4-carboxylic acid, zinc acetate and N,N'-dimethylformamide solution were mixed and then hydrothermally reacted to generate M-CPs coordination polymerization hybrid material; S2, mixing the carboxylated cellulose nanofiber suspension and sodium alginate and freeze-drying the mixture to obtain a SNF polymer, and immersing the aerogel in a calcium chloride solution for cross-linking to obtain a cross-linked SNF polymer; S3, soaking the cross-linked SNF polymer obtained in step S2 in a mixed solution containing N-isopropylacrylamide, N,N'-methylenebisacrylamide, an initiator, and CNTs, and after vacuum drying, quickly dripping N,N,N',N'-tetramethylethylenediamine therein, and polymerizing at room temperature after freezing polymerization to obtain ASNF hydrogel; S4, adding the M-CPs coordination polymerization hybrid material and ASNF hydrogel into an aqueous solution containing acrylamide, bisacrylamide, and ammonium persulfate to form a suspension; S5, dispersing the mesoporous SiO2 microspheres into the suspension formed in step S4, and freeze-drying to obtain ASNF-M / SiO2@CPs hybrid copolymer gel; There is no order of precedence for steps S1 and S2.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of 4'-phosphinobiphenyl-4-carboxylic acid to zinc acetate is 25-30:30-35; in the N,N'-dimethylformamide solution, the volume ratio of N,N'-dimethylformamide to water is 9:

1.

3. The preparation method according to claim 1, characterized in that: In step S3, in the mixed solution, the mass ratio of the cross-linked SNF polymer, N-isopropylacrylamide, N,N'-methylenebisacrylamide, initiator and CNTs is 300-350:1000:2:25:1-2.

4. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the M-CPs coordination polymerization hybrid material and the ASNF hydrogel is 15-20:

280.

5. The preparation method according to claim 4, characterized in that: In step S4, the mass ratio of acrylamide, bisacrylamide and ammonium persulfate is 18-20:1:20-25, and the concentration of acrylamide is 0.12-0.18 g / ml.

6. The preparation method according to claim 1, characterized in that: In step S5, the concentration of SiO2 microspheres in the suspension is 0.2-0.3 g / ml.

7. The preparation method according to claim 1, characterized in that: In step S3, the polymerization is performed at -18°C for 18-20 hours and then at room temperature for 4-5 hours.

8. The preparation method according to claim 1, characterized in that: In step S5, the mixture is frozen at -80°C for 24 hours and then dried at room temperature for 48 hours.

9. The preparation method according to claim 1, characterized in that: In step S1, 4'-phosphinobiphenyl-4-carboxylic acid is prepared by the following method: (1) Add 200 mL of dried tetrahydrofuran (THF) to 4,4'-biphenyl dibromide under Ar gas protection and stir for 5-10 minutes to obtain solution a; (2) cooling solution a to -78°C, adding butyl lithium dropwise, stirring vigorously, and then standing at low temperature to obtain solution b; (3) adding excess concentrated HCl dropwise to solution b, stirring vigorously, then adding dichloromethane dropwise, stirring for 5-10 minutes, and filtering to obtain a white solid powder product 4'-bromobiphenyl-4-carboxylic acid; (4) After mixing 4'-bromobiphenyl-4-carboxylic acid and methanol, concentrated H2SO4 was added dropwise, and the mixture was refluxed at 75°C overnight. After cooling, the methanol was removed by spinning and filtered to obtain a white solid powder product, 4'-bromobiphenyl-4-carboxylic acid methyl ester; (5) 4'-bromobiphenyl-4-carboxylic acid methyl ester, diethyl phosphate, palladium acetate, triethylamine, triphenylphosphine and dried toluene were added to a three-necked flask in sequence, and refluxed overnight under Ar gas protection to obtain a turbid solution c; (6) Add activated carbon to solution c for reflux decolorization, filter out the black solid, wash and filter with 1:2 ethyl acetate-petroleum ether solution, and dry to obtain a milky white solid powder of 4'-diethyl phosphite-bromobiphenyl-4-carboxylic acid methyl ester; (7) 4'-Diethylphosphite-bromobiphenyl-4-carboxylic acid methyl ester, deionized water, concentrated HCl and dimethyl sulfoxide (DMSO) were added into a round-bottom flask in sequence, refluxed at 100° C. overnight, and filtered and dried to obtain 4'-phosphinobiphenyl-4-carboxylic acid.

10. An ASNF-M / SiO2@CPs hybrid copolymer gel prepared by the preparation method according to any one of claims 1 to 9.